Strict Liability of Marketplace Platforms for Consumer Losses Due to the Circulation of Illegal Goods - Ditya Putri Wulansari; Fuji Cantika; Danil Mustafa; Nessie Gusriani; Radatun Dwi Nazria (CV WAHANA PUBLIKASI, 2026)
This article examines the strict liability of marketplace platforms for consumer losses arising from the circulation of illegal goods in electronic transactions. The study uses normative legal research with statutory, conceptual, and prescriptive approaches to consumer protection law, electronic information law, electronic commerce regulations, and platform governance literature. Existing Indonesian rules still rely on fragmented consumer-protection, electronic-commerce, and electronic-system duties, while consumers often face difficulty identifying sellers, proving platform fault, and obtaining timely recovery. The article finds that the relationship between marketplace platforms, sellers, and consumers is not a single ordinary sale contract, but a layered electronic transaction consisting of a consumer-seller sale, a platform-seller intermediation agreement, and a platform-consumer service relationship. This legal configuration makes the platform more than a passive intermediary when it designs the transaction environment, controls seller access, processes payment, ranks listings, stores transaction data, and provides complaint mechanisms. The strict liability principle is therefore justified when illegal goods circulate through a marketplace system and cause consumer losses, especially where the platform failed to prevent, detect, remove, or remedy prohibited products. The article proposes a qualified strict liability model based on platform control, risk creation, statutory duty, causation, and remedial capacity. It concludes that strict liability should strengthen consumer recovery without eliminating the seller's primary responsibility or turning platform responsibility into unlimited liability.